Memaknai politik dalam dua matra A. A. Yewangoe: Suatu basis teologis bagi keterlibatan gereja dalam dunia politik di Indonesia - Wowor, Alter Imanuel (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
Discussions about political theology in Indonesia became increasingly popular after the reformation events. The pros and cons regarding the church's involvement in various political affairs seem to be a hot issue that continues to emerge in various political events in Indonesia. The lack of uniform attitudes and interpretations of the many churches in Indonesia regarding what politics is, how churches do politics, and the relationship between politics and the church makes this problem even more complicated. This research aims to produce a study that can be used as a reference or on a theological basis regarding the issue of church involvement in politics in the Indonesian context based on a review of Andreas Anangguru Yewangoe's thoughts. The research method used in this research is descriptive analysis with a literature study approach. The thesis is that the church's involvement in politics is a response to a divine call and is not facultative. The Gospel is an